An Appraisal of the Invasion of Midwest State By the Biafran Secessionists Government and Liberation During the Period of Nigerian Civil War August 9-September 20, 1967 - Ediagbonya Michael; Duyile William Abiodun (Britain International for Academic Research (BIAR) Publisher, 2023)
This paper examines the invasion of Midwest state by the Biafran Secessionists Government in August 9, 1967. The occupation of the state by the rebels also came to focus. The consequence of the invasion and liberation of the state by the federal troops were demonstrated. Data for the study was obtained through oral interview as primary sources and the secondary sources like books, newspapers, articles, journals, theses, projects and dissertation were also used. It was found that August 9 on which the people of the Midwest celebrate the yearly anniversary of the creation of their state was the day rebel troops invaded the state. It was demonstrated that while the state was invaded by the rebels on August 9, 1967, September 20, 1967, the people regained freedom. It was also found that Ojukwu’s conquest and occupation of the Midwest was a miscalculated strategy to prolong the war and annex Southern Nigeria. In conclusion, the economy of the state was badly affected by the disruption of trade and movement of the population in search of safety.